COMPARATIVE STUDY OF EARLY GROWTH PERFORMANCE OF NAKED NECK, NORMAL AND FRIZZLE-FEATHERED NIGERIAN NATIVE CHICKENS REARED UNDER INTENSIVE SYSTEM IN GUINEA SAVANNAH - Audu, Mercy O.; Momoh, O. Michael; Ukwu, Henry O. (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigated the early growth performance of naked neck, normal and frizzle-feathered Nigerian native chickens, under intensive system. 150 chicks, comprising 50 chicks from each genotype, were used in a 3 X 2 factorial arrangement in a Completely Randomized Design (CRD), with genotype and sex as factors of interest. Data were collected on hatch weight, weekly body weights, and total weight gain. The result showed no significant genotype effect (P>0.05) on hatch weight and body weight at week one. From week 3 to week 8, naked neck and frizzle-feathered chicks had comparable body weights, which differed significantly (P
Keywords: Genotypes; Growth; Native chicken; Guinea savannah; Body weight